POTRET MEDIA ISLAM DALAM FILM BERTEMA TERORISME - Midih Saputra (JURNAL INDO-ISLAMIKA, 2018)
The media can shape and influence public opinion and the means of disseminating certain issues, through messages and news on television, radio, newspapers as well as films can construct public perceptions, films are like two sides of a knife that have both good and bad effects. Referring to films with a background of violence or acts of terrorism which use Islamic attributes or symbols can certainly be analyzed from the side of the image shown as well as the sound by using visual semiotic theory referring to Barthes' theory parsing the meaning contained in objects both denotation and connotation. take lexia-lexia or text unit which is an instrument of refusal in three titles of films with the theme of terrorism simultaneously. The film which is the object of this research consists of; Valley of The Wolves, Iraq. 2006, Act of Valor. 2012, Sector 4. 2014. This research is a qualitative research that is descriptive and comparatively defined as a research procedure that produces data in the form of words or words from people and observable behavior.